2023
DOI: 10.48550/arxiv.2302.06858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trainability Enhancement of Parameterized Quantum Circuits via Reduced-Domain Parameter Initialization

Abstract: Parameterized quantum circuits (PQCs) have been widely used as a machine learning model to explore the potential of achieving quantum advantages for various tasks. However, the training of PQCs is notoriously challenging owing to the phenomenon of plateaus and/or the existence of (exponentially) many spurious local minima. In this work, we propose an efficient parameter initialization strategy with theoretical guarantees. We prove that if the initial domain of each parameter is reduced inversely proportional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Indeed, finding good initial parameters is one of the most effective solutions to the vanishing gradient problem in classical neural networks [19,20]. Likewise, studies have shown that a quantum model can also have large initial gradients when parameters are initialized smartly [21][22][23][24][25][26][27][28]. However, most of the suggested initialization methods cannot be easily applied to large and deep circuits as they rely on heuristics developed from small circuits [22,23] or the proven lower bounds of gradient magnitudes are still too small for a deep circuit [25,26].…”
mentioning
confidence: 99%
“…Indeed, finding good initial parameters is one of the most effective solutions to the vanishing gradient problem in classical neural networks [19,20]. Likewise, studies have shown that a quantum model can also have large initial gradients when parameters are initialized smartly [21][22][23][24][25][26][27][28]. However, most of the suggested initialization methods cannot be easily applied to large and deep circuits as they rely on heuristics developed from small circuits [22,23] or the proven lower bounds of gradient magnitudes are still too small for a deep circuit [25,26].…”
mentioning
confidence: 99%